Financial constraints and moral hazard: The case of franchising - Ying Fan; Kai-Uwe Kühn; Francine Lafontaine (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
Financial constraints are an important impediment to the growth of small businesses. We study theoretically and empirically how the financial constraints of agents affect their decisions to exert effort, and, hence the organizational decisions and growth of principals, in the context of franchising. We find that a 30 percent decrease in average collateralizable housing wealth in a region delays chains' entry into franchising by 0.28 years on average, 9 percent of the average waiting time, and slows their growth by around 10 percent, leading to a 10 percent reduction in franchised chain employment.
Keywords: L14; L22; D22; D82; L8; 330; R&D; contracting; incentives; principal-agent; empirical; collateralizable housing wealth; entry; growth